The Role of Imagination and Ideology in Defining Culture in the Works of Edward Bond - Kaleem, Aqsa (Journal of Research in Humanities, 2023)
Understanding the human mind and its intricacies is what informs the works of the prolific septuagenarian contemporary British playwright, Edward Bond. His distinctive approach toward this effort is redolent with historical and contemporary references. These alert the readers and the audience to the evolution and devolution of the human psyche as a result of cause and effect and the intransigent nature of injustice and violence. The human cultural memory is eidetic to the extent that it is itself capable of understanding that humans are born radically innocent as Bond writes in the “Commentary on the War Plays,” published in his sixth volume of plays, “Radical innocence is the psyche’s conviction of its right to live, and of its conviction that it is not responsible for the suffering it finds in the world or that such things can be” (251). According to Bond the human imagination, combined with reason is the basis of all ideologies which create a culture. The successful integration of these elements results in humanism whereas the human imaginations failure to integrate reason with itself leads to violence and injustice pervading the annals of history and cultural epochs. In the book Edward Bond and the Dramatic Child, Bill Roper in his essay titled “Imagination and Self in Edward Bond’s Work,” writes, “Importantly, human value, not fiction, is at the heart of the human mind’s use of imagination to understand the world and society; imagination and reason together construct the human self and open the routes of corruption and innocence, through which the self is continually created” (Davis 126). Hence the purpose of this research was to analyse the 138 Aqsa kaleem symbiotic relationship between the human imagination and reason in creating ideologies which define culture and its problems.